Comparison between two‐dimensional and three‐dimensional quantitative coronary angiography for the prediction of functional severity in true bifurcation lesions: Insights from the randomized DK‐CRUSH II, III, and IV trials. (15th February 2016) - Zhang, Yao‐Jun; Zhu, Hao; Shi, Shun‐Yi; Muramatsu, Takashi; Pan, Dao‐Rong; Ye, Fei; Zhang, Jun‐Jie; Tian, Nai‐Liang; Bourantas, Christos V.; Chen, Shao‐Liang
Abstract : Objective: This study investigated the diagnostic accuracy of three‐dimensional quantitative coronary angiography (3D‐QCA) compared with conventional 2D‐QCA for predicting functional severity assessed by fractional flow reserve (FFR) for true bifurcation lesions. Methods: Based on pooled data from the randomized DK‐CRUSH II, III, and IV trials, we evaluated the patients with true bifurcation lesions who underwent coronary angiography together with functional evaluations using FFR in both the main vessel and the side branch. Off‐line 2D‐ and 3D‐QCA analyses were conducted using dedicated bifurcation QCA analysis software. Measurements of minimum lumen diameter (MLD), percentage diameter stenosis (% DS), and minimum lumen area (MLA) were compared between 2D‐ and 3D‐QCA, and we evaluated their predictive values of functionally significant FFR. Results: Ninety patients were eligible for enrollment in the present study. In the main vessel, MLA measured by 3D‐QCA was the most accurate predictor of FFR <0.75 (C statistic 0.85, P < 0.001), while MLD measured by 2D‐QCA was a similarly accurate predictor (C statistic 0.85, P < 0.001). In the side branch, the best metrics for predicting FFR <0.75 were % DS measured by 2D‐QCA with a C statistic value of 0.91 ( P < 0.001) and MLA measured by 3D‐QCA with a C statistic value of 0.81 ( P < 0.001). However, both 2D‐ and 3D‐QCA metrics exhibited low accuracies for predicting FFR <0.75 in intermediate bifurcation lesions. Conclusions: 3D‐QCA analysis for true bifurcation lesions did not improve the predictive accuracy of functionally significant FFR compared with 2D‐QCA analysis. In lesions with intermediate stenosis, the diagnostic performance of both 2D‐ and 3D‐QCA‐derived measurements in differentiating functional severity is limited. © 2016 Wiley Periodicals, Inc.